The Role of Technology in Preventing Bullying in Educational Environments - A'zdom, Muhammad Khofidul (Journal of Strategy and Transformation in Educational Management, 2024)
Preventing bullying in educational environments is becoming increasingly important with the growing use of technology in daily life. This article explores how technology can be used as an effective tool to detect, report, and prevent bullying behavior in schools. We analyze various technologies, such as mobile applications and social media platforms, as well as strategies for their implementation in reducing bullying incidents. The study also identifies ethical and practical challenges associated with the application of technology in the context of bullying prevention. By considering relevant literature and case studies, this article provides a comprehensive view of the role of technology in supporting a safe and inclusive educational environment.